INFLUENCE OF ENGLISH LANGUAGE ON IKWERRE LANGUAGE IN PORT HARCOURT METROOLIS OF RIVERS STATE - Ezi-Nlerum , Blessing; Ken-Maduako, Ibiere (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
This study was concerned with the assessment of the influence of English Language on Ikwerre Language within Port Harcourt Metropolis of Rivers State, Nigeria. Its objectives were to investigate the role of parents, schools and government in protecting the Ikwerre Language from being killed (destroyed) by the English Language and to ascertain the level of proficiency in the use of the native language amongst the Ikwerre parents and children. Data were elicited with the use of the questionnaire and interview schedule. The sample size of the study was made up of 400 respondents which were selected through the random sampling technique. Frequently, percentage and mean were used for the analyses of data which were obtained from the field survey. Results indicated that the level of proficiency in the use of the native language amongst Ikwerre parents was 20%, while that of children was 5%, bringing the pooled proficiency value to 12.50%. The following results were obtained: Parents, schools and government have not done much to protect the Ikwerre Language spoken in Port Harcourt metropolis from being endangered by the English Language. In order to prevent the Ikwerre Language from going into extinction in the area, the study recommends that the language should be frequently spoken at home by parents to their children to increase proficiency in its use. The school and government should also enforce the use of the language of the environment as a medium of instruction for the first three years as is stated in the National Policy on Education provisions.